Virtual reality-based wheelchair simulators: A scoping review. Issue 6 (1st November 2020) - Arlati, Sara; Colombo, Vera; Ferrigno, Giancarlo; Sacchetti, Rinaldo; Sacco, Marco
ABSTRACT: Sense of presence (SoP) has recently emerged as one of the key elements promoting the effectiveness of virtual reality-based training programs. In the context of wheelchair simulators (WSs), the effectiveness of the simulation has been sought using different perception and interaction devices, providing the end-users with different levels of SoP. We performed a scoping review searching scientific and grey literature databases with the aim of assessing the extent of published research dealing with SoP and effectiveness of WSs. Sixty-two articles, describing 29 WSs, were included in the review. In spite of promising results, the high heterogeneity of the employed technological solutions, of the training programs and of their outcomes precluded drawing definitive conclusions about the optimal solution for the enhancement of SoP and thus of WSs' effectiveness. Future research should focus on controlled trials in order to help researchers in assessing the most suitable technologies and methodologies for the application of WSs in clinical practice.